Efecto del biocarbón y microorganismos en la producción y estado fitosanitario de banano orgánico en la parroquia La Victoria - Azuero Gaona, Bryan Roger (Machala : Universidad Técnica de Machala, 2020)
Bananas are the main agricultural crop in El Ecuador, providing substantial economic income to the country and is a job-generating activity for many families. Our country located on the equatorial line, has the best edaphoclimatic conditions, making this the Ecuadorian banana is credited with being the best in quality, promoting a great demand worldwide, placing it as the first exporting country. Taking into account the above, the average production boxes/ha/year is very low compared to other countries in the region where organic bananas are also produced, so this research topic was raised to look for better alternatives, the overall objective of which was to find a mechanism to increase productivity and resistance to the attack of pests and diseases in banana cultivation through the application of biocarbon and mountain microorganisms. The research was developed in the farm “La Playa” located in the parish of La Victoria, the experimental design that was proposed in the field was randomized blocks with five treatments and ten repetitions choosing only plants +2, performed on two types of soil; clay and sandy loam: T1 = witness; T2 = 10 applications of 50 g biochar + 50 ml of ME; T3 = 10 applications of 100 g biochar + 100 ml ME; T4 = (10 applications of 50 g of biochar + 50 ml ME), + 50 g Potassium sulfate (K2SO4) + 10g Fossil Shell Agro in maceration applied to the pseudostem and T5 = 1 application of 1000 g biochar + 1 lt ME. The variables to study were: Cluster Weight (PR), Spine Weight (PRq), Processed Ratio (RP), Hand Weight (PM), Number of Hands (NM), Number of Fingers (ND), Last Hand Calibration (CUM), Calibration hand of the sun (CSM), Number of Leaves (NH), Evalutionary State (EE), Age Clusters (ER), Weekly Growth cm (CS), Percentage of live roots at the beginning of the investigation (RVI), Percentage of live roots at the end of the investigation (RVF) and Return (Ret). The values obtained in the investigation show very significant data in the types of soil, in the clay loam the variables that were significant among the treatments according to the ANOVA statistical analysis were: PR the T4 with (73.90 lb), RP the T4 with (1.52), NM the T4 with an average of (8.30) but most of their clusters had 9 hands, CUM the T5 with (41.20), CMS the T5 with ( 44.60), in relation to RVI and RVF the T4 with (97.58%), Ret the T4 with (1.75) and in the B/C ratio the T4 with (2.78). In the sandy soil the variables that had a significant difference between the treatments according to the ANOVA statistical analysis were: PRq the T5 with (5.06 lb), RP the T3 with (0.813), ND the T4 with (24.8), in the relation of RVI and RVF the T3 having at the beginning (28.90%) and at the end (80.02%) was the The best treatment obtained in completely healthy roots, in the B / C ratio, T2 and T3 obtained the same value of (1.41). Concluding that the application of biocarbon + ME considerably improves productivity in the cultivation of organic bananas, in clay loam soil it is recommended to apply the doses of T4 for the reason that in the majority of the variables taken it was the one that obtained the best result and the one that will generate greater economic gains, in the sandy soil it is recommended to apply any dose of either T2 and T3 because at the moment of obtaining the B/C ratio they are the same values.
El banano es el principal cultivo agrícola en El Ecuador, aporta de forma sustancial ingresos económicos al país y es una actividad generadora de empleos para muchas familias. Nuestro país ubicado en la línea ecuatorial, posee las mejores condiciones edafoclimáticas, haciendo esto que al banano ecuatoriano se le atribuya ser el mejor en calidad, propiciando una gran demanda a nivel mundial, ubicándolo como el primer país exportador. Teniendo en cuenta lo antes mencionado, la media de producción cajas/ha/año es muy baja comparada con otros países de la región donde también se produce banano orgánico, por lo cual se planteó este tema de investigación para buscar mejores alternativas, cuyo objetivo general fue el de encontrar un mecanismo para incrementar la productividad y la resistencia al ataque de plagas y enfermedades en el cultivo de banano mediante la aplicación de biocarbón y microorganismos de montaña. La investigación fue desarrollada en la hacienda “La Playa” ubicada en la parroquia La Victoria, el diseño experimental que se planteó en campo fue en bloques al azar con cinco tratamientos y diez repeticiones escogiendo únicamente plantas +2, realizado en dos tipos de suelo; franco arcilloso y arenoso: T1= testigo; T2 = 10 aplicaciones de 50 g biocarbón + 50 ml de ME; T3 = 10 aplicaciones de 100 g biocarbón + 100 ml ME; T4 = (10 aplicaciones de 50 g de biocarbón+ 50 ml ME), + 50 g Sulfato de potasio (K2SO4 ) + 10g Fossil Shell Agro en maceración aplicado al pseudotallo y T5 = 1 aplicación de 1000 g biocarbón + 1 lt ME. Las variables a estudiar fueron: Peso de racimo (PR), Peso de raquis (PRq), Ratio Procesado (RP), Peso de la Mano (PM), Número de Manos (NM), Número de Dedos (ND), Calibración ultima mano (CUM), Calibración mano del sol (CSM), Número de Hojas (NH), Estado Evolutivo (EE), Edad Racimos (ER), Crecimiento Semanal cm (CS), Porcentaje de raíces vivas al inicio de la investigación (RVI), Porcentaje de raíces vivas al final de la investigación (RVF) y Retorno (Ret). Los valores obtenidos en la investigación muestran datos muy significativos en los tipos de suelo, en el franco arcillo las variables que hubo significancia entre los tratamientos según el análisis estadístico ANOVA fueron: PR el T4 con (73.90 lb), RP el T4 con (1.52), NM el T4 con una media de (8.30) pero la mayoría de sus racimos tuvieron 9 manos, CUM el T5 con (41.20), CMS el T5 con (44.60), en relación de RVI y RVF el T4 con (97.58%), Ret el T4 con (1.75) y en la relación B/C el T4 con (2.78). En el suelo arenoso las variables que hubo diferencia significativa entre los tratamientos según el análisis estadístico ANOVA fueron: PRq el T5 con (506 lb), RP el T3 con (0.813), ND el T4 con (24.8), en la relación de RVI y RVF el T3 teniendo al inicio (28.90%) y al final (80.02%) fue el mejor tratamiento que obtuvo en raíces completamente sanas, en la relación B/C el T2 y T3 obtuvieron el mismo valor de (1.41). Concluyendo que la aplicación de biocarbón + ME mejora considerablemente la productividad en el cultivo de banano orgánico, en el suelo franco arcilloso se recomienda aplicar las dosis del T4 por el motivo que en las mayorías de las variables tomadas fue el que mejor resultado se obtuvo y el que generara mayor ganancias económicas, en el suelo arenoso se recomienda aplicar cualquier dosis ya sea del T2 y T3 por que al momento de obtener la relación de B/C son los mismo valores.
Keywords: BIOCARBÓN; MICROORGANISMOS; PRODUCCIÓN; COSTO